The lost girls : a vampire revenge story - Hartl, Sonia (Page Street Publishing Co., 2021)
Holly Liddell has been stuck with crimped hair since 1987 when she agreed to let her boyfriend, Elton, turn her into a vampire. But when he ditches her at a gas station a few decades into their eternity together, she realizes that being young forever actually means working graveyard shifts at Taco Bell, sleeping in seedy motels, and being supernaturally compelled to follow your ex from town to town, at least until Holly meets Elton's other exes, who invite Holly to join them in their quest to kill Elton before he can trick another girl into eternal adolescence.